HPLC Determination of Chlorobenzene in Benzene Sulfonylchloride for Industrial use by High Performance Liquid Chromatography - Xiulan, Cai; Mei, Zhu; Yuna, Wei; Hongzhen, Lian (Asian Journal of Chemistry, 2010)
A reversed phase high performance liquid chromatographic method has been developed for the determination of chlorobenzene in industrial benzene sulfonylchloride. Analysis was accomplished in a Kromasil C18 column with methanol-water (65 : 35, v/v) or acetonitrilewater (60 : 40, v/v) as mobile phase and detection was performed by UV absorption at a wavelength of 215 nm. The chromatographic behaviour and separation performance of samples determined were compared under two elution conditions chosen. The method is rapid, accurate, reliable and has been successfully applied for the quality control analysis of benzene sulfonylchloride in the laboratories of some chemical plants.